Effects of suberogorgin and its derivates on learning and memory in mice - Peng Wen-Duo; Xu Shi-Bo; Peng Xun (Acta Pharmacologica Sinica, 2016)
AIM: To study the relationship between the effects of suberogorgin (Sub) and its derivates on memory and their anti-acetylcholinesterase (AChE) actions. METHODS: The step-down latency (SDL) and the escape latency (EL) of mice were determined at the same time in a passive avoidance task after Sub, N-suberogorgamide-N-N-dicyclohexyl urea (Sub-DU), or N-cyclohexyl suberogorgamide (N-CS) was injected i.p. The AChE activities in brain hemogenates were determined with colorimetry. RESULTS: Sub 1.9, Sub-DU 3.0, or physostigmine (Phys) 0.15 mg.kg-1 obviously lengthened the SDL by 195%, 271%, and 210%, and shortened the EL by 56%, 61%, and 33%, and the two formers inhibited the brain AChE activities by 17% and 19%, respectively in aging (3-4 months) mice. These actions were decreased in a dose-dependent manner when Sub or Sub-DU was increased to 2.9-4.3 or 4.5-6.7 mg.kg-1 respectively. Sub 1.9, Sub-DU 2.0, and Phys 0.15 mg.kg-1 also lengthened the SDL by 187%, 209%, and 152%, and shortened the EL by 52%, 62%, and 57%, respectively in aged (12-14 months) mice. Sub 1.3-1.9, Sub-DU 0.9-2.0, or Phys 0.15 mg.kg-1 reversed the cycloheximide- or scopolamine-induced disruptions of memory retention. No obvious effect of N-CS on the acquisition of memory and the AChE activity in mice was observed. CONCLUSION: The improvements of Sub and Sub-DU on memory were chiefly related to their anti-AChE actions.